APPLICATION OF NEW INNOVATIVE METHODS IN TEACHING ECONOMIC SUBJECTS IN GENERAL SECONDARY SCHOOLS - Abdushukurova Sevinch Akramjonovna (American Journals, 2024)
In this article, the teaching of economic sciences in general secondary schools will be raised to a new level, the opportunities for providing quality education, the formation of economic and entrepreneurial knowledge skills of schoolchildren, new innovative methods during the lesson will be discussed. methods of using educational methods and recommendations are given.
Keywords: Educational system, innovative approach, quality, quality education, innovative educational methods (excursion lesson, combined lesson, lesson conference), educational technologies, ensuring the quality of education.